Breastfeeding experiences of women with perinatal mental health problems: a systematic review and thematic synthesis - Hayley Billings; Janet Horsman; Hora Soltani; Rachael Louise Spencer (BMC, 2024)
Abstract Background Despite its known benefits, breastfeeding rates among mothers with perinatal mental health conditions are staggeringly low. Systematic evidence on experiences of breastfeeding among women with perinatal mental health conditions is limited. This systematic review was designed to synthesise existing literature on breastfeeding experiences of women with a wide range of perinatal mental health conditions. Methods A systematic search of five databases was carried out considering published qualitative research between 2003 and November 2021. Two reviewers conducted study selection, data extraction and critical appraisal of included studies independently and data were synthesised thematically. Results Seventeen articles were included in this review. These included a variety of perinatal mental health conditions (e.g., postnatal depression, post-traumatic stress disorders, previous severe mental illnesses, eating disorders and obsessive-compulsive disorders). The emerging themes and subthemes included: (1) Vulnerabilities: Expectations versus reality; Self-perception as a mother; Isolation. (2) Positive outcomes: Bonding and closeness; Sense of achievement. (3) Challenges: Striving for control; Inconsistent advice and lack of support; Concerns over medication safety; and Perceived impact on milk quality and supply. Conclusions Positive breastfeeding experiences of mothers with perinatal mental health conditions can mediate positive outcomes such as enhanced mother/infant bonding, increased self-esteem, and a perceived potential for healing. Alternatively, a lack of consistent support and advice from healthcare professionals, particularly around health concerns and medication safety, can lead to feelings of confusion, negatively impact breastfeeding choices, and potentially aggravate perinatal mental health symptoms. Appropriate support, adequate breastfeeding education, and clear advice, particularly around medication safety, are required to improve breastfeeding experiences for women with varied perinatal mental health conditions.